X. Biblical Archaeology - Gray, J. (1963)
ed. by H. H. Rowley; spez. I. The Cradles of Culture: Egypt and Mesopotamia (246-254); II. Israel’s Neighbours (254-259); III: Archaeology and Biblical Events (259-272).